Заметки о некоторых центральноазиатских видах рода Catocala (Lepidoptera, Noctuidae) с описанием нового вида из Каракалпакии (Узбекистан) - Ключко, З.Ф. (Вестник зоологии, 1993)
The genus Catocala is subdivided into 2 groups, recognizible by male genitalia sclerotization characteristics and valvae dorsal margin shape, as based upon 10 species type-material examination. Lectotypes of C. kusnezovi Pung. (1914), C.neglecta Stgr. (1888) and C. timur A. B.-H. (1907) are designated. C. aralica sp. n. is described on a single male from Karakalpakia (Takhta-Kupyr). Holotype is deposited in the Lepidoptera collection, Kiev University Zoological Museum.